Utilizing Online Education in Florida to Meet Mandated Class Size Limitations - Kari Ann Mattox (Educational Considerations, 2012)
With the passage of a state constitutional amendment in 2002, Florida school districts faced the challenge of meeting class size mandates in core subjects, such as mathematics, English, and science by the 2010-2011 school year, or face financial penalties.
Keywords: education; Florida; students; school districts; mandates; class; limitations; Online Learning